Use of statistical methods to identify layers of volcanic soils with the cone penetration test in a place located within Universidad de Costa Rica, Montes de Oca, San José, Costa Rica - Mora, Rolando (2011)
Univariate (RI yT) and multivariate (D2) statistical methods have been applied to set limits of layers on a CPTU sounding, held in soils composed of fills and volcanic deposits. The results include layered models that con- sider different resolutions and reduced application subjective criteria for establishing the boundaries of the layers. It is considered that the index D2 provides more accurate results.